The oncologic safety of left colectomy with modified complete mesocolic excision for distal transverse colon cancer: Comparison with descending colon cancer. Issue 11 (November 2021) - Song, Inho; Park, Ji Won; Lim, Han-kin; Kim, Myung Jo; Kim, Min Jung; Park, Sung-Chan; Oh, Jae Hwan; Oh, Heung-Kwon; Kim, Duck-Woo; Kang, Sung-Bum; Ryoo, Seung-Bum; Jeong, Seung-Yong; et al.
Abstract: Background: The optimal surgical approach for distal transverse colon cancer has not been well established. This study aimed to evaluate the oncologic safety of left colectomy with a modified complete mesocolic excision for distal transverse colon cancer as compared with descending colon cancer. Material and methods: This study involved 383 patients who underwent left colectomy with modified complete mesocolic excision for non-metastatic distal transverse and splenic flexure colon (transverse group, N = 110) and descending colon cancer (descending group, N = 237) from 3 institutions. Recurrence-free survival (RFS) and overall survival (OS) were compared between the two groups. Results: Baseline characteristics between the two groups were similar except for the length of the distal margin (transverse group = 11.0 cm vs descending group = 9.0 cm, p = 0.004). During a median follow-up of 47.0 months, RFS and OS were not different between the transverse and descending groups (5-year RFS: 82% vs 71%, p = 0.139; 5-year OS: 83% vs 79%, p = 0.416, respectively). In multivariable analysis, RFS and OS were not different between the two groups (transverse group vs. descending group: adjusted hazard ratio [aHR] = 1.557, 95% CI = 0.786–3.084, p = 0.204; aHR = 1.251, 95% CI = 0.530–2.952, p = 0.609). Conclusion: The oncologic outcomes of left colectomy with a modified complete mesocolic excision of distal transverse colon cancer were comparable to those of descending colon cancer. Left colectomy with a modified complete mesocolic excision can be an acceptable surgical treatment for distal transverse colon cancer. Highlights: ● Optimal surgical approach for distal transverse colon cancer has not been well established ● Left colectomy for descending colon cancer was demonstrated oncological safety ● The oncologic outcomes of left colectomy for the distal transverse colon were comparable ● Left colectomy can be an acceptable surgical treatment for distal transverse colon cancer.